An efficient phase-field model for fatigue fracture in ductile materials. (1st February 2020) - Seiler, Martha; Linse, Thomas; Hantschke, Peter; Kästner, Markus
Highlights: A new phase-field model for fatigue crack initiation and propagation is proposed. It minimises computational effort due to a combination with a classic fatigue concept. A revaluation technique replaces an elasto-plastic material model. The model can reproduce Paris behaviour. Abstract: Fatigue fracture in ductile materials, e.g. metals, is caused by cyclic plasticity. Especially regarding the high numbers of load cycles, plastic material models resolving the full loading path are computationally very demanding. Herein, a model with particularly small computational effort is presented. It provides a macroscopic, phenomenological description of fatigue fracture by combining the phase-field method for brittle fracture with a classic durability concept. A local lifetime variable is obtained, which degrades the fracture resistance progressively. By deriving the stress-strain path from cyclic material characteristics, only one increment per load cycle is needed at maximum. The model allows to describe fatigue crack initiation, propagation and residual fracture and can reproduce Paris behaviour.